Sub-Arctic populations of European lobster (Homarus gammarus) in Northern Norway. - Jorstad, K.E.; Prodöhl, Paulo; Agnalt, A.-L.; Hughes, Maria; Apostolidis, A.; Triantaphyllidis, A.; Farestveit, E.; Kristiansen, T.; Mercer, J.; Sversand, T. (2004)
The European lobster is distributed throughout the south and western regions of the Norwegian coast. A previous lobster allozyme investigation (1993) in the Tysfjord region, north of the Arctic Circle demonstrated that the lobster population from this region was genetically different from lobster samples collected in other parts of Norway. More detailed investigation including supplementary extensive sampling and additional allozyme, microsatellite and mtDNA analyses are reported here. This investigation supports the genetic distinctness of the Tysfjord population and shows that this is mainly due to a reduction (60ï¿½70%) in gene diversity (observed heterozygosities and number of alleles) compared with lobsters from more southern regions. In addition to the Tysfjord region, the comprehensive sampling also included lobsters found in the adjacent Nordfolda fjord system. Genetic analyses provided evidence for significant differences between the lobster populations of Tysfjord and Nordfolda, even though they are separated by a coastal distance of only 142 km. The two populations were also different with regards to several biological characteristics such as body size. The genetic difference between these two geographically close populations is likely to be due to the local hydrological conditions, preventing larval dispersal between the fjord systems. Assessment of lobster abundance in the north-west region suggests that the sub-arctic lobster populations are geographically isolated.